How To Implement Employee Work Discipline at PT. EG - Afriyani, Fauzia (Yayasan Pendidikan Belajar Berdikari, 2024)
Finding out how employee work discipline is applied at PT. Enrichment Grup (EG) is the goal of this study. Examine the reasons behind employee indiscipline issues and suggest solutions for the company's disciplinary issues. Qualitative approaches are the approach taken in this study. Interviews and observations were used as data collecting strategies. Purposive sampling was used to select five staff representatives who were thought to be qualified to answer questions about the research topic as research informants. The research findings, after the analytical procedure, indicate that EG personnel have a poor degree of discipline, necessitating additional improvement. This company's disciplinary issues include workers who show up late for work, significant absenteeism rates without warning, and delays in completing tasks. In order for employees to better comply with company regulations, leaders must be more assertive with them, put new regulations in writing, and ensure that employees are aware of the importance of respecting time even in the event that the company implements new regulations. Because labor will yield the best results when a disciplined attitude is maintained.